Artificial Intelligence (AI) for Sustainable Institutional Food Systems: Implementation of AI Tools for School Nutrition Program Management in the United States of America - Camaréna, Stéphanie (Frontiers in Sustainable Food Systems, 2022)
School food programs can improve the nutritional status at community level, and can be a powerful tool to facilitate a transition to sustainable food systems, particularly through their purchasing methods and meal/waste management. Artificial Intelligence (AI) can enable or inhibit transitions to sustainability, due to its capacity to facilitate transformational change and disruption. Thus, AI can have major impacts on achieving the United Nations' Sustainable Development Goals (SDGs), including those related to food systems. This paper focuses on critically exploring different aspects during the implementation of a software project in US schools that used AI techniques to enable agility and provide healthy food options for schoolchildren. Participant observation, semi-structured interviews, and document analysis were used to inform the case study and uncover the new processes developed using the technology. As a key barrier to the effective management of school food programs and nutrition is the administrative load associated with statutory compliance, this case study demonstrates the difference that AI-powered tools can make in alleviating the weight of administrative processes. An Information and Communication Technology (ICT)-enabled boundary spanning framework is used to extend the case study toward an analysis of the systems, boundaries, relationships and perspectives which starts mapping the areas where the private sector, public institutions and civil society can meet to fast-track sustainable transition activities, particularly in the context of food systems. This article presents some possible approaches to facilitating these activities, inviting policy makers to bridge the gap with businesses and use business agility to support common societal goals to achieve sustainable food systems.